Pengaruh Pembebasan Sanksi Administratif Pajak Kendaraan Bermotor Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Roda Dua (R2) (Studi Kasus Pada Kantor Bersama Samsat Lamongan) - Rina Febrianti Miftahur Rohmah; Umar Yeni Suyanto; Rina Sulistyowati (JEMAP, 2022)
This study aims to examine and analyze the effect of exemption from motor vehicle tax administrative sanctions and service quality on the compliance of two-wheeled motorized vehicle taxpayers at the Lamongan Samsat , either partially or simultaneously. The number of samples used is 100 motor vehicle taxpayers which is calculated using the slovin formula with the method of determining the sample, namely incidental sampling. The data analysis technique used is multiple linear regression analysis using the SPSS 24 program. The results show that partially there is the effect of exemption from motor vehicle tax administrative sanctions and has a positive and significant effect on motor vehicle taxpayer compliance. In the service quality variable there is a positive and significant effect on motor vehicle taxpayer compliance. Meanwhile, simultaneously the exemption of motor vehicle tax administrative sanctions and service quality have a positive and significant impact on the compliance of two-wheeled motorized vehicle taxpayers at the Lamongan Samsat.